G118(P) Associations between postnatal growth rates and cognitive outcomes at age 16 years in infants born small-for-gestational-age at term. (12th March 2018) - Hallinan, E; Fewtrell, M; Palit, V; Winyard, P; Bedford, H
Abstract : Background: Rapid post-natal growth is associated with increased risk of adult cardiovascular and metabolic disease. In preterm infants, rapid post-natal growth is also associated with improved long-term cognition. Small-for-gestational-age (SGA) term infants have increased risk of adverse long-term cognitive outcomes compared to appropriate-for-gestational-age (AGA) term infants; they are also prone to rapid post-natal 'catch-up' growth. It is therefore important to understand whether rapid post-natal growth in this population confers any long-term cognitive advantage, and balance this with recognised metabolic risks. Aims: To investigate associations between post-natal growth in term-SGA infants and cognitive outcomes in adolescence. Methods: 60 term-SGA infants were followed-up from birth to 16 years. Weight, head circumference (HC) and length were measured at enrolment, 6, 12 and 26 weeks, 9 and 18 months and 16 years. Measurements were converted to standard deviation scores (SDS) and changes in SDS between time points calculated. Cognitive outcomes were measured at 16 years to assess global intelligence (IQ); literacy and academic attainment (Wechsler Individual Attainment Test–reading and maths subtests); and executive functioning (Stroop Colour-Word test). Univariate and multivariate analyses explored associations between growth and cognitive outcomes. Results: In univariate analysis HC growth from 0–6 weeks was significantly associated with increased Full Scale and Verbal IQ (FSIQ and VIQ). A 1-SDS increase in HC growth over this period was associated with a 7.10-point increase in FSIQ (95% CI: 1.15 to 13.04, p=0.02) and a 10.82-point increase in VIQ (95% CI: 3.31 to 18.34), p=0.006. However, after adjustment for confounders in multivariate models, HC growth no longer significantly predicted cognitive outcome, whilst maternal education was a significant predictor of IQ, reading and maths scores. Conclusions: A positive association between HC growth from birth to 6 weeks and later IQ was seen. However, this was not significant after adjustment for confounding factors, possibly due to under-powering. Maternal education was a significant predictor of cognitive outcomes at 16 years. Given the recognised risks associated with rapid post-natal growth, this study does not support promoting rapid growth in term-SGA infants.